No letters on exco posts yet, says Azizan - News Straits, Times (New Straits Times, 2012)
ALOR STAR: Menteri Besar Datuk Seri Azizan Abdul Razak said letters of offer and reappointments for state councillors for the 2012-2013 term had yet to be issued.